Comparing the Effectiveness and Safety of Giving Fentanyl or Ketamine Intranasally during Phacoemulsification Surgery: Intranasal Fentanyl VS Intranasal Ketamine in Phacoemulsification Cataract Surgery: Intranasal Fentanyl VS Intranasal Ketamine in Phacoemulsification Cataract Surgery - Shetabi, Hamidreza; Peyman , Alireza; Piudeh, Farzan (Galen Medical Journal, 2023)
Background:Phacoemulsification is the main method of cataract surgery in developed countries. Due to the importance of appropriate analgesia and the immobility of the participants throughout the procedure, the study aimed to assess the impact of intranasal ketamine vs. intranasal fentanyl on the quality of sedation and analgesia in phacoemulsification surgery. Materials and Methods: This double-blinded study was carried out on participants who underwent cataract surgery in Faiz Hospital, Isfahan, Iran. Eighty subjects were randomly assigned to two groups of 40 receiving ketamine at a dosage of 1.5 mg/kg intranasally (Intranasal Ketamine (INK) group) or fentanyl at 1.5 μg/kg nasally (Intranasal Fentanyl (INF) group). The drugs were administered through the nasal passage 15 minutes before the operation. The primary outcomes were a difference in the quality of sedation and pain relief between groups during the procedure and recovery unit. Secondary outcomes were cardiovascular parameters, side effects, the need for sedative rescues, and changes in vital signs. Results: During the study, 25 patients (62.5%) in the INK cohort and 19 patients (47.5%) in the INF cohort had no pain. In the INK group, 22 (55%) and in the INF group 20 (50.0%) patients achieved optimal sedation (Ramsay sedation score 4). There was no discernible disparity observed between the two cohorts in terms of the quality of sedation (P=0.071), receipt of rescue dosage of propofol (P=0.601), hemodynamic parameters (P>0.05), and side effects during treatment Operation (P=0.542) and in recovery (P=0.104), patient (P=0.098) and surgeon (P=0.120) satisfaction, operative time (P=0.082), and duration of stay in recovery (P=0.110). Conclusion: Although INK was more effective than INF in reducing pain and achieving optimal sedation in cataract surgery, it was not significantly superior to INF.